석류피 에탄올 추출물의 항치아우식 활성 - 유용욱(Yong Ouk You); 유현희(Hyeon Hee Yu) (동의생리병리학회지, 2007)
Dental caries is a major worldwide oral disease problem. Streptococcus mutans (S. mutans) plays an important role in the information of dental plaque and it is being noticed as major causative bacteria of dental caries. Therefore, the development of more effective, substantial and safe preventive agents against dental caries is strongly required. In the present study, inhibitory effects of the ethanol extract of the husk of pomegranate (Punica granatum L.) on the growth, acid production, adhesion and water-insoluble glucan synthesis of Streptococcus mutans (S. mutans) were examined. The ethanol extract of pomegranate husk (250 - 4000 ${μ}$g/ml) significantly lowered the growth of S. mutans in a dose dependent manner. The acid production of S. mutans were inhibited by the presence of ethanol extract of pomegranate husk (500 - 4000 ${μ}$g/ml) significantly. The ethanol extract of pomegranate husk (5000 - 4000 ${μ}$g/ml) also significantly lowered the adherence of S. mutans. In water-insoluble glucan synthesis assay, 1000 - 4000 ${μ}$g/ml of the ethanol extract of pomegranate husk significantly inhibited the formation of water-insoluble glucan. These results suggest that pomegranate husk may inhibit the caries-inducing properties of S. mutans. Further studies are necessary to clarify the active constituents of pomegranate husk responsible for such biomolecular activities.